Holographic Methods for Strongly Coupled Systems - Bigazzi, Francesco; Cotrone, Aldo L.; Evans, Nick; Kiritsis, Elias; Liu, Hong; Nunez, Carlos; Skenderis, Kostas (Il Colle di Galileo, 2016)
The “holographic correspondence” – the mapping between quantum field theories and higher dimensional theories of gravity – can be used as a tool to understand strongly interacting systems describing relevant phenomena in nature. Counting on the participation of many of the top world experts in the field, the Workshop succeeded in bringing together an international community of theoretical physicists, providing an overview and assessment of recent progress and identifying priorities and coordinated efforts for a better understanding of strongly coupled phenomena using holographic methods. World-renowned scientists, together with brilliant young researchers, presented their recent results on applications of holographic methods to QCD, condensed matter systems and general quantum field theories. The Workshop hosted the “Gauge/Gravity Duality 2015” conference, the last edition of a series of bi-annual meetings of the European Science Foundation network HoloGrav, also sponsored by a COST action.